The application of Microtremor Survey Method in investigating the geological formation of Singapore - Muhammad Azri Omar. (2012)
In the recent study of seismic activities, the Microtremor Survey Method (MSM) has become a very much interesting tool in estimating subsurface soil structure for better understanding of the ground response by amplification factor. This research has been undertaken by many around the world mainly because of the advantages it offers as oppose to conventional site investigation such as boring. The method is also known to be low in cost and non-destructive in nature. The entire project will plan to investigate the geological formation of Singapore as well as estimating subsurface soil profile using the MSM. Moreover, the Spatial Autocorrelation (SPAC) method will be applied to show how the recorded data will be selected and processed to estimate Rayleigh wave dispersion curve, thereafter estimating the subsurface soil layers. A comparison between the results obtained from SPAC analysis as well as borehole information will also be shown to check for consistency. Apart from that, a short research on the selection analysis of data segment lengths will be discussed as to whether there will be significant impact towards generating the phase velocity profile diagrams. Comparison between smaller and larger number of data will be illustrated and explained to show any crucial significant effect on the potential end result. The data lengths that will be chosen are 4096, 8192 and 16384 number of data. Finally, a summary findings as well as a discussion on some of the result inconsistencies will be presented. This research can be used in future study such as identifying the amplification factor as well as the simulation of hazardous effect during a potential earthquake event.